T. J. Luce y J. Woodman (eds.), Tacitus and the Tacitean Tradition, Princeton, New Jersey, Princeton University Press, 1993, XV + 207 pp. (Minerva, 2019)
Review: T. J. Luce y J. Woodman (eds.), Tacitus and the Tacitean Tradition, Princeton, New Jersey, Princeton University Press, 1993, XV + 207 pp.